EULAR recommendation for the management of rheumatoid arthritis (2013): glucocorticoid use - N.V. Chichasova (Современная ревматология)
The role of glucocorticoids (GCs) in the current strategy of treating rheumatoid arthritis (RA) according to the EULAR 2013 recommendation is discussed. The main studies focused on GCs since they started to be used to treat RA are reviewed. The difficulties, advantages, and draw- backs of using GCs to treat RA, as well as possibilities to affect progression of destruction in small joints of the hands and feet, are discussed. Since new data have recently been obtained, EULAR recommendations 2013 for the management of RA patients states the following for GCs: «The use low doses of GCs (combined with one or several disease-modifying anti-rheumatic drugs) should be considered as a component of the treatment strategy during the first six months of the disease». It is particularly emphasized that GCs should be abandoned as soon as it is pos- sible from the clinical viewpoint. The term «low dose of GC» means prednisolone prescribed at a dose ≤7.5 mg/day.